Evaluation, Productivity and Competition of Brachiaria decumbens, Centrosema pubescens and Clitoria ternatea as Sole and Mixed Cropping Pattern in Peatlandâs - Arsyadi, Ali; Luki, Abdullah; PDMH, Karti; MA, Chozin; DA, Astuti (Indonesian Journal of Animal and Veterinary Sciences, 2014)
This study was carried out to determine the productivity, competition indices and nutrient content of Brachiaria decumbens (grass), Centrosema pubescens and Clitoria ternatea (legumes) as sole and mixed cropping system in peatland in Pekanbaru, Indonesia from October 2011 to November 2012. The experiment was set up in randomized complete block design with five treatments and three blocks as replication. Five treatments compared: B. decumbens sole cropping (Bd), C. pubescens sole cropping (Cp), C. ternatea sole cropping (Ct), B..decumbens and C. pubescens mixed cropping (Bd+Cp) and B. decumbens and C..ternatea mixed cropping (Bd+Ct). The dry matter (DM) yield of B. decumbens was significantly (P<0.05) increased by mixed cropping. B. decumbens DM yield in C. pubescens intercrop increased by 147.9% and in C. ternatea intercrop increased by 74.1% compare to sole B. decumbens. Land equivalent ratio (LER) value range from 1.04 (Bd+Ct) to 1.58 (Bd+Cp). The crowding coefficient (K) value of B. decumbens in both mixed croping system was higher than K value of C. pubescens and C. ternatea. The total K value for Bd+Cp was higher than Bd+Ct. The competition ratio (CR) value of B. decumbens mixed cropping with C. pubescens and C. ternatea were.>1. The aggressivity (A) value of B. decumbens in both mixed cropping was positive. The crude protein (CP) content of B.decumbens did not significantly (P>0.05) increased by mixed cropping with legumes. Intercropping with B. decumbens significantly (P<0.05) decreased CP content of C. ternatea. Meanwhile neutral detergent fibre (NDF) and acid detergent fibre (ADF) content of B. decumbens did not decrease by intercropping with C.pubescens and C. ternatea. In conclusion, mixed cropping with C. pubescens and C. ternatea in peatland increased DM yield of B. decumbens. Mixed cropping with B. decumbens did not influence DM yield of C. pubescens and decreased DM yield and CP content of C..ternatea. Mixed cropping of B. decumbens with C. pubescens and B. decumbens with C..ternatea in peatland did not increase total DM yield of forage per unit area of land and nutrition contents of forage. B. decumbens was more competitive and dominant than C..pubescens and C. ternatea in peatland. Key Words: Cropping System, Forage, Nutrient Contents, Yield, Peatland